Assessing the Level of Knowledge and Attitude of the Saudi Population in Taif City towards Varicoceles Prevention and Treatment - Badr, Samir Ahmad; Almalki, Khaled Abdulrahman; Alhathla, Thamer Eid M; Alotaibi, Abdulelah Mastour; Turkistani, Mohammed Adel; Alghamdi, Abdulrahman Abdullah; Albaqami, Mohammed Qazan (International Journal of Innovative Research in Medical Science, 2021)
Background: Varicocele is a common problem in males that drastically affect their reproductive health. There is some way to reduce or prevent this problem from occurrence. However, the level of knowledge of the general public towards these measures is unclear. Methods: A cross-sectional observational survey study that was carried out in Saudi Arabia using an online self-developed questionnaire that was distributed, via a link to Google form, to the general public. All adult literate citizens and residents in Taif city, Saudi Arabia were eligible for inclusion in this study. Only completed surveys were included in the analysis. Data were represented in the form of frequencies (number of responders) and valid percentages for categorical variables. ANOVA test was utilized to compare means between different subgroups. All P values < 0.05 were considered statistically significant. Result: A total of 275 participants responded to the survey. The mean score for knowledge was 10.01±4.305, with a minimum score of zero and a maximum score of eighteen. Females showed a significantly higher mean score (13.67±3.114) (p-value = 0.002). Single participants showed significantly higher mean score (10.26±4.176) (p-value= 0.04). Responders with a university degree had a higher average score (10.35±4.257) (p-value=0.002), and participants with a medical background had a higher average score (11.48±3.401) (p-value<0.001). Conclusion: A poor level of knowledge and attitude towards varicocele prevention and treatment were observed in Saudi Arabia. Further studies are required to figure out the level of knowledge and behaviors on a national level, and to explore the reasons behind this poor knowledge about varicocele.